A review of application status and replacement progress of refrigerants in the Chinese cold chain industry. (August 2021) - Gao, Enyuan; Cui, Qi; Jing, Huaqian; Zhang, Zhiyuan; Zhang, Xiaosong
Highlights: The application status and replacement progress of refrigerants in the Chinese cold chain industry are reviewed. The controlled refrigerants represented by R22, R404A, R507A, and R134a are still used in large quantities. R717 is unassailable used in large-sized cold chain equipment of China in the future. The application importance of R744 and R290 is becoming increasingly prominent in China. China is actively meeting its refrigerant replacement commitments in terms of policy, regulation, and technology. Abstract: In the context of refrigerant replacement and the Chinese international commitments on carbon emissions reaching peak and carbon neutral, this paper provides an overview of the application status and the replacement progress of refrigerants in key cold chain equipment of China. The review results show that refrigerant replacement in the Chinese cold chain industry is slower than in the air-conditioning industry. Controlled refrigerants such as R22, R404A, R507A, and R134a are still used in large quantities and dominate the market. Natural refrigerant R744 and R290 are still used on a tiny scale. For large-sized cold chain equipment, R717 or in combination with R744, has proven to be safe, environmentally friendly, and efficient, makes it unassailable in the future. For small-sized cold chain equipment, R22, R404A, and R507A are dominant currently. The replacement of R404A and R507A is an outstanding issue that should be focused on and addressed in the future. R744 booster systems are rarely used in large supermarkets in China, and the gap between Europe and Japan is huge. Future efforts are needed both in terms of policy and technology. For display cabinets, freezers, and domestic refrigerators, controlled refrigerants such as R22, R404A, and R134a currently dominate. Pleasantly, R290 is gaining momentum, and the future development is extremely promising in this field. Opportunities and challenges accompany the future development of the Chinese cold chain industry. China has completed the current phase of HCFCs replacements as committed. Efforts are still needed in the next phase of HCFCs and HFCs replacements.